Resection interventions in the treatment of hepatocellular cancer in a specialized surgery center - V. A. Pelts; V. E. Tropin; V. A. Shatalin (Acta Biomedica Scientifica, 2023)
Background. The relevance of the treatment of hepatocellular cancer (HCC) is determined by a significant increase in the incidence rate and its high prevalence among primary malignant hepatic tumors.The aim of the study. To summarize the experience of providing specialized medical care to patients with hepatocellular cancer.Methods. We studied the direct results of treatment of patients with primary hepatic cancer treated at the Kuzbass Regional Hepatological Center for the period from January 2015 to August 2022. The materials for the study were medical records of patients with an established diagnosis of primary hepatic cancer, surgical records, results of pathohistologic examination. The exclusion criterion was diagnosed cholangiocellular carcinoma.Results. During the period from 2015 to 2022, 59 patients with primary hepatic cancer were treated at the Kuzbass Regional Hepatological Center. Among them, hepatocellular cancer was diagnosed in 48 cases, cholangiocellular cancer – in 11 cases; radical surgery was performed in 12 patients with hepatocellular cancer; fatal outcome was noted in 1 (2.1 %) patient, complications in the postoperative period developed in 5 (41.7 %) cases and were ranked as I-3, IIIb-1 and IVb-1 according to Clavien – Dindo classification.Conclusion. The degree of risk of severe post-resection hepatic failure should be considered one of the main criteria in choosing a strategy for radical surgical treatment. New surgical approaches (laparoscopic vascular isolation of the portal blood flow, using temporary hemostasis in laparoscopic hepatic resections and the device for its implementation) in resection surgery of primary hepatic cancer can improve the immediate results of treatment.